Pelatihan dan Pendampingan Pembuatan Sabun Cuci Bagi Ibu-Ibu PKK di Desa Cadek Banda Aceh - Maknuni, Jauharil; Annisaturrahmi (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
Community service is an activity that must be developed in the midst of society, this activity will help the community to progress and develop, one of which is the service carried out by the Cadek KPM team, the program designed is training and assistance in making soap for PKK women in Cadek village, training activities were carried out at the Cadek meunasah, who were present during the soap making process not only from PKK women but the community and children participated, the community was very enthusiastic during the training process. This training has 4 methods, first place observation, lecture method, practical method, and discussion method (question and answer). The purpose of the research is to empower the community to have their own business and even if it is small, this will certainly help the family financially. From the results of the study, it was found that during the training process the PKK women were very enthusiastic, especially when the tools and materials had been provided at the table. The community is very excited to follow the steps of making laundry soap. The obstacles faced during the training process for the children who participated made the activity less conducive because it was noisy, so the process of making laundry soap was repeated up to 3 times. The impact of this training is expected to increase the welfare that can be felt by the family, of course there will be additional income by implementing this simple training at home or in a group of people.